1994
DOI: 10.1136/thx.49.7.684
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in men with primary ciliary dyskinesia presenting with respiratory infection.

Abstract: Background -Primary ciliary dyskinesia is characterised by chronic rhinosinusitis, chronic bronchial sepsis (usually with bronchiectasis), dextrocardia in approximately 50% of cases, and male infertility. The latter, described in patients attending infertility clinics, results from immotile but viable spermatozoa. Experience in a respiratory clinic suggests that infertility in men is not invariable. Methods -The seminal fluid of 12 men with primary ciliary dyskinesia, six with dextrocardia, who presented conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 19 publications
1
63
0
7
Order By: Relevance
“…Although male infertility is said to be common in PCD, it is not universal [Munro et al, 1994]. Indeed, one of the DNAH11 PCD patients reported by Schwabe [Schwabe et al, 2008] had apparently fathered two children without medical assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although male infertility is said to be common in PCD, it is not universal [Munro et al, 1994]. Indeed, one of the DNAH11 PCD patients reported by Schwabe [Schwabe et al, 2008] had apparently fathered two children without medical assistance.…”
Section: Discussionmentioning
confidence: 99%
“…The sperm count is typically normal, but sperm are immotile or their motility is severely limited [55,82]. In some reports, up to 50% of males with PCD are fertile [55].…”
Section: Other Systemsmentioning
confidence: 99%
“…The sperm count is typically normal, but sperm are immotile or their motility is severely limited [55,82]. In some reports, up to 50% of males with PCD are fertile [55]. Some females with PCD exhibit normal fertility, but others show impaired fertility and an increased risk of ectopic pregnancy because of impaired ciliary function in the oviduct [82].…”
Section: Other Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review suggested that 58% of women and 100% of men were infertile, but the included studies were highly heterogeneous [1]. MUNRO et al [85] reported azoospermia and oligospermia in a small sample size, with normal motility seen in only one patient. RAIDT et al [86] demonstrated that the motor protein composition of fallopian tube cilia is similar to that of respiratory cilia.…”
Section: Fertilitymentioning
confidence: 99%